2018
DOI: 10.1007/s00421-018-3835-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of two different doses of ultraviolet-A light exposure on nitric oxide metabolites and cardiorespiratory outcomes

Abstract: PurposeThe present study investigated different doses of ultraviolet-A (UV-A) light on plasma nitric oxide metabolites and cardiorespiratory variables.MethodsTen healthy male participants completed three experimental conditions, 7 days apart. Participants were exposed to no light (CON); 10 J cm2 (15 min) of UV-A light (UVA10) and 20 J cm2 (30 min) of UV-A light (UVA20) in a randomized order. Plasma nitrite [NO2−] and nitrate [NO3−] concentrations, blood pressure (BP), and heart rate (HR) were recorded before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Other UVR Phototherapies Five studies were identified in which treatments with UVA and/or UVB were administered for varying lengths of time (between 1 and 12 weeks) and doses (both erythemal and suberythemal were tested) to mainly 'healthy' populations of adults [32][33][34][35] (except for those who were individuals with psoriasis 36 ) ( Table 4). In three studies, mean BMI was ≥25 kg/m 2 , [33][34][35] with BMI not reported in the other papers. 32,36 Skin type was reported in three (of the five) studies, two of which reported findings from individuals who were mainly Fitzpatrick skin types II-III.…”
Section: Psoralen Ultraviolet a Phototherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Other UVR Phototherapies Five studies were identified in which treatments with UVA and/or UVB were administered for varying lengths of time (between 1 and 12 weeks) and doses (both erythemal and suberythemal were tested) to mainly 'healthy' populations of adults [32][33][34][35] (except for those who were individuals with psoriasis 36 ) ( Table 4). In three studies, mean BMI was ≥25 kg/m 2 , [33][34][35] with BMI not reported in the other papers. 32,36 Skin type was reported in three (of the five) studies, two of which reported findings from individuals who were mainly Fitzpatrick skin types II-III.…”
Section: Psoralen Ultraviolet a Phototherapymentioning
confidence: 99%
“…36 Finally, in healthy young adults, reduced oxygen utilisation and metabolic rate were observed along with increases in blood nitrite, immediately (early, short-term, ≤30 min) after exposure to UVA. 35…”
Section: Psoralen Ultraviolet a Phototherapymentioning
confidence: 99%
“…Considering these findings, it is plausible to assume an inverse relationship between synthesis of NO and its metabolites via sunlight exposure and plasma aldosterone levels, although we could not suggest the exact amount of NO and its metabolites synthesized via sunlight exposure. However, the evidence of NO on BP reduction is still weak, although there is a plausible impact on metabolic function [42].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of human skin to UV-A radiation has also been proposed to acutely increase NO production (50,54,58), but it may (50,58) or may not (54) reduce blood pressure. The NO-producing effect of UV-A appears to be mediated by liberation of NO via photolysis of cutaneous nitrite stores (58) and is independent of NOS (50).…”
Section: Nonfolate Nonvitamin D Effects Of Uvr On Skin Vascular Functionmentioning
confidence: 99%